When the bough breaks ... over children ; our environment [videorecording] - Moore, Lawrence; Stamp, Robbie (Oley, Pa. Bullfrog Films, 1990)
Explores how environmental neglect and ignorance threatens the lives of millions of children in Poland, U.S., India, Bolivia, U.K. and Sudan.
VHS.
Narrator, Janet Suzman.
Keywords: Environment and children; Children